"Understanding the costs and benefits of short term international volunteerism" : exploring the benefits and potential harms with regard to short-term international volunteer service in Cape Town - Hatane, Luann Mabakoena (Department of Sociology, 2016)
An increasing interest in international volunteer service (IVS) has resulted in a large number of companies offering volunteers from developed countries the opportunity to work with non-governmental organisations (NGOs) and service organisations in developing countries. Amidst a growing body of research into the impacts and benefits of different IVS models, there remains limited literature available on whether IVS can be harmful. A study, entitled 'AIDS orphan tourism: A threat to young children in residential care' by Richter and Norman has given some prominence to IVS harm in residential child care settings and, in part, motivated this study. This descriptive case study explores how benefits and harm in shortterm international volunteer service (STIVS) is understood and experienced by both international volunteers (IVs) and local host organisations (LHOs). The study places emphasis on whether IVs had considered harm prior to starting their IVS, and whether IVs and LHOs shared similar understandings or concerns to those identified in the Richter and Norman study. A problem-driven framework, drawing on quantitative and qualitative approaches, was used to explore the understanding of harm and benefit by IVs and LHOs. The study adopted a mixed methods approach to obtain data from a variety of sources. Univariate statistics, percentages, thematic and regression analysis were used to analyse the data. Data was collected between the 27th May and the 31st August 2014 in Cape Town, South Africa. Cross- Cultural Solutions South Africa (CCS-SA) provided the study site, with all field work for this study integrated into the regular operational, monitoring and evaluation processes of the CCS-SA programme.